Pediatric Board Study Guide A Last Minute Review - Naga, Osama (Springer International Publishing : Imprint: Springer, 2015)
Covering the most frequently asked and tested points on the pediatric board exam, Pediatric Board Study Guide offers a quick review of specific diseases and conditions clinicians need to know during the patient encounter.  Chapters cover the American Board of Pediatrics core content specifications and are authored by experts on the key subspecialties.  Also featured are Last Minute Review Tables, which include clinical case scenarios and high-yield facts.  Easy-to-use, richly illustrated and comprehensive, clinicians will find this resource to be an invaluable reference.